2018
DOI: 10.1002/ange.201801332
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Evolution of Crosslinked and Extractable Material in an Oil‐Based Paint Model System

Abstract: The construction of mechanistic models for the autoxidation of fatty acid or ester substrates found in oil paint binders is ac hallenging undertaking due to the complexity of the large crosslinked species that form, and the small molecules that volatilize. Building models that capture this product diversity are made possible by automating the process of network generation. This work presents am icrokinetic model for the autoxidation of ethyl linoleate catalyzedbycobalt(II) 2ethyl hexanoate.T he mechanism size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…One experiment showed that, after catalysing the formation of oligomeric structures during curing of ethyl linoleate, in the long term a Co based drier promoted a series of decomposition reactions which overwhelmed the polymerisation reactions 37 . Similar phenomena may take place in paints containing Co-based pigments where, after an initial stage in which drying and subsequently polymerisation has taken place, other reaction pathways become dominant, leading to the oxidative degradation/fragmentation of the paint film 35,37 .…”
Section: Pigments and Additivesmentioning
confidence: 59%
See 1 more Smart Citation
“…One experiment showed that, after catalysing the formation of oligomeric structures during curing of ethyl linoleate, in the long term a Co based drier promoted a series of decomposition reactions which overwhelmed the polymerisation reactions 37 . Similar phenomena may take place in paints containing Co-based pigments where, after an initial stage in which drying and subsequently polymerisation has taken place, other reaction pathways become dominant, leading to the oxidative degradation/fragmentation of the paint film 35,37 .…”
Section: Pigments and Additivesmentioning
confidence: 59%
“…Termination reactions resulting from the recombination of radicals allow the formation of nonradical products, such as relatively unstable peroxides, or the relatively stable products of crosslinking reactions and oxidation 35 . When peroxides are formed, these will react further with time, undergoing scission and forming alcoxyl radicals (RO•).…”
Section: Oil Fractionmentioning
confidence: 99%
“…At current stage of art, its detailed kinetics can be approached only by mechanistic models available by automating the process of network generation. 166,167 Recent microkinetic model for the autoxidation of ethyl linoleate catalyzed by cobalt(II) 2-ethylhexanoate, well reproduces the key reaction outcome and enables to explore effect of temperature and catalyst concentration. 167…”
Section: Crosslinking Reactions and Side Productsmentioning
confidence: 96%
“…The curing of a drying oil—a glycerolipid based on polyunsaturated fatty acids—involves autoxidative radical chain reactions, which are light initiated, and metal catalysed 1 – 6 . Upon curing, fatty acids in triglycerides undergo several transformations, which entail the formation of epoxy, hydroxyl, oxo and carbonyl moieties, as well as new C–C and C–O–C bonds 1 , 4 , 6 , 7 . Small oxidised molecules are formed by oxidative degradation of the fatty acid chains upon evolution of peroxyl and alkoxyl moieties 4 , 6 , and are quickly lost by evaporation 8 .…”
Section: Introductionmentioning
confidence: 99%